Gaya Kepemimpinan, Motivasi, Tambahan Penghasilan Dan Disiplin Kerja: Sebuah Kajian Tentang Kinerja Pegawai - Zulkarnain Basir; Raizal Adhimsyah; Rizka Prayoga; Firmansyah (Jurnal Ilmiah Bongaya, 2023)
This research has the aims and objectives of measuring the influence of leadership style, motivation, additional income and work discipline on employee performance. The population in this study were 30 employees with ASN status who worked at the Tomoni sub-district office, East Luwu district. A saturated sampling technique (census) was used to determine respondents, so there were 30 respondents in this research sample and they were collected through a questionnaire and then analyzed using a multiple linear regression model. The research results found that both individually and collectively, leadership style, motivation, additional income and work discipline had a positive and significant effect on employee performance. Meanwhile, the contribution of influence can be seen from the customized R square value obtained where the value obtained is 0.664 or it can be said that the contribution of the influence of leadership style, motivation, additional income and work discipline on employee performance is 66.4% while the rest is influenced by other variables which were not studied. in this research. . Keywords: Leadership Style, Motivation, Additional Income, Work Discipline, Employee Performance.